Composting of fish waste and its phytotoxicity effects. Issue 10 (11th October 2021) - Valente, Beatriz Simões; Otto, Iliane Müller; Demarco, Carolina Faccio; Bunde, Dienifer Aline Braun; Ávila, Fernanda Dias; Guidoni, Lucas Lourenço Gastiglioni; Pieniz, Simone; Correa, Érico Kunde; Andreazza, Robson
Abstract: This work aimed to evaluate the composting of the mixture of residues from fish filleting, using sawdust as a structuring material as an alternative for stabilization, through physical-chemical analysis and phytotoxicity. The experiment was carried out in a composter 1.10 m long, 1.50 m wide, and 1.20 m high and presenting 2.50 m in total height, which received the mixture of fish filleting wastes and sawdust in a5:3 ratio, respectively. The results demonstrated that composting in cells is an efficient alternative for the decomposition of the mixture of fish filleting and sawdust residues. The rapid decomposition of fish waste and the low C/N ratio harms the development of thermophilic microorganisms during the composting of the mixture of fish filleting and sawdust residues. The compaction of the sawdust layers and the absence of stirring in the composting method in cells collaborate for the compost to need a time greater than 60 days to be recommended as simple organic fertilizer. The biomass stirring is necessary so that sawdust can be considered a good structuring agent. The phytotoxicity test should be taken into account by the Normative Instruction n° 25/2009 as an indicator of compost maturity.